UJI AKTIVITAS ANTI TUBERKULOSIS H37RV EKSTRAK DAN FRAKSI TANAMAN MERBAU (Intsia bijuga) - Ayik Rosita Puspaningtyas; Dian Agung Pangaribowo; Tasya Salsabila Multazam (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
Tuberculosis (TB) is recognized as one of the top ten potentially fatal diseases. TB is caused by the bacterium Mycobacterium tuberculosis, which attacks the lungs. Indonesia has a variety of plants that can potentially serve as a treatment, one of which is the merbau plant (Intsia bijuga). The purpose of this study was to determine the anti-tuberculosis activity of extracts and fractions of merbau stem bark against Mycobacterium tuberculosis H27Rv bacteria based on IC50 values. Merbau bark was extracted using maceration method using methanol solvent. Then fractionated using n-hexane, dichloromethane (DCM) and ethyl acetate solvents. Next was phytochemical screening test using KLT method. In vitro anti-tuberculosis activity test using resazurin colorimetric method with concentrations of 25, 100, 500, and 1000 µg/mL. The results of the in vitro anti-tuberculosis test showed that the n-hexane fraction had the smallest IC50 of the extracts and other fractions with a result of 2,920 µg/mL, which indicates that it has the best activity as an anti-tuberculosis agent. Screening results from the n-hexane fraction showed positive for alkaloid and flavonoid compounds.